The Need for E-Module Development for Early Childhood Cognitive and Language Development Courses - Uswatul Hasni; Hendra Sofyan; Rizki Surya Amanda (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
The use of appropriate learning resources plays a crucial role in supporting the achievement of learning objectives. Currently, the available resources in the Cognitive and Language Development in Early Childhood course have not fully facilitated students in comprehensively and deeply understanding the material. This study aims to analyze the needs for developing an e-module in this course as an effort to enhance learning effectiveness. This research employed a descriptive qualitative approach. The subjects consisted of 15 third-semester students from the Early Childhood Teacher Education Program who had completed the relevant course. Data were collected through semi-structured interviews and open surveys, then analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results revealed that students require an e-module containing structured materials aligned with the Semester Learning Plan (SLP), equipped with instructional videos, illustrative images, case-based exercises, and project-based learning methods. The conclusion highlights the importance of developing an e-module as an alternative learning source that supports students’ independent, interactive, and contextual learning processes. The implication is that this e-module is expected to become an effective medium for strengthening learning outcomes based on students’ needs and the characteristics of the subject matter.